Cellulose degradation and electricity generation using Microbial Fuel Cell (MFC) by locally isolated gram negative bacillus - Faisal Ghazali, Mohd. Nazlee (2012)
To integrate knowledge and progress among academicians, researchers, industries, corporate organizations and interest groups. To enhance our global academic, scientific and professional networking. To internalize the importance of Biosustainability and Green Technology.